Advances in the Study of circRNAs in Hematological Malignancies - Du, Jingyi; Jia, Feiyu; Wang, Lijuan (Frontiers in Oncology, 2022)
Circular RNAs (circRNAs) are non–protein-coding RNAs that have a circular structure and do not possess a 5` cap or 3` poly-A tail. Their structure is more stable than that of linear RNAs, and they are difficult to deform via hydrolysis. Advancements in measurement technology such as RNA sequencing have enabled the detection of circRNAs in various eukaryotes in both in vitro and in vivo studies. Most circRNAs are considered microRNA (miRNA) sponges. circRNAs act as tumor suppressors or oncogenes during the development of many tumors and are emerging as new diagnostic and prognostic biomarkers. They also affect resistance to certain chemotherapy drugs such as imatinib. The objective of this review is to investigate the expression and clinical significance of circRNAs in hematological malignancies. We will also explore the effect of circRNAs on proliferation and apoptosis in hematological malignancy cells and their possible use as biomarkers or targets to determine prognoses. The current literature indicates that circRNAs may provide new therapeutic strategies for patients with hematologic malignancies.